Motivations for Internationalization of Higher Education: A Study of Multiple Cases in a Higher Education Denominational International System - Everson Muckenberger; Irene Kazumi Miura (Arizona State University, 2015)
One of the reactions or responses of Higher Education Institutions (HEIs) to globalization has been internationalization. There are studies on motivations or rationales that drive public and private HEIs to internationalization. However, little is known about rationales for internationalization among denominational institutions and even less about denominational HEIs that are part of an international higher education system. Thus, a study of multiple cases was conducted, taking six HEIs, located in different regions of the World, maintained by the same denomination and that, together with other HEIs, form an international confessional higher education system, called System Σ. The identified rationales partially confirm the rationales proposed by Knight (2004 and 2008), but specifically denominational rationales were also identified. As for the rationales at the system level, they also resemble denominational rationales.